Methodology of Organizing Individual Work of Students from Drawing Geometry within the Credit System at the Pedagogical Higher Education - M. Ergashev (Genius Journals, 2022)
In the article, Drawing provides scientific information about the creative thinking and organization of individual work of students during the teaching of geometry sciences in higher education institutions, as well as the development of computer technologies and technological computer games with the help of tools and methods of intensive development and updating the world views in the field of intellectual IT
Keywords: Drawing geometry and individual work; engineering graphics; creative thinking; intellectual computer games